Effects of pressure overload, left ventricular hypertrophy on beta-adrenergic receptors, and responsiveness to catecholamines. - Vatner, D E (1984)
Pressure overload left ventricular (LV) hypertrophy was produced by banding the ascending aorta of puppies and allowing them to grow to adulthood. LV free wall weight per body weight increased by 87% from a normal value of 3.23 +/- 0.19 g/kg. Hemodynamic studies of conscious dogs with LV hypertrophy and of normal, conscious dogs without LV hypertrophy showed similar base-line values for mean arterial pressure, heart rate, and LV end-diastolic pressure and diameter. LV systolic pressure was significantly greater, P less than 0.01, and LV stroke shortening was significantly lss, P less than 0.01, in the LV hypertrophy group. In both normal and LV hypertrophy groups, increasing bolus doses of norepinephrine or isoproterenol produced equivalent changes in LV dP/dt. beta-adrenergic receptor binding studies with [3H]-dihydroalprenolol ( [3H]DHA) indicated that the density of binding sites was significantly elevated, P less than 0.01, in the hypertrophied LV plasma membranes (111 +/- 8.8, n = 8), as compared with normal LV (61 +/- 5.6 fmol/mg protein, n = 11). The receptor affinity decreased, i.e., disassociation constant (KD) increased, selectively in the LV of the hypertrophy group; the KD in the normal LV was 6.8 +/- 0.7 nM compared with 10.7 +/- 1.8 nM in the hypertrophied LV. These effects were observed only in the LV of the LV hypertrophy group and not in the right ventricles from the same dogs. The plasma membrane marker, 5' -nucleotidase activity, was slightly lower per milligram protein in the LV hypertrophy group, indicating that the differences in beta-adrenergic receptor binding and affinity were not due to an increase in plasma membrane protein in the LV hypertrophy group. The EC50 for isoproterenol-stimulated adenylate cyclase activity was similar in both the right and left ventricles and in the two groups. However, maximal-stimulated adenylate cyclase was lower in the hypertrophied left ventricle. Plasma catecholamines were similar in the normal and hypertrophied groups, but myocardial norepinephrine was depressed in the dogs with LV hypertrophy (163 +/- 48 pg/mg) compared with normal dogs (835 +/- 166 pg/mg). Thus, severe, but compensated LV hypertrophy, induced by aortic banding in puppies, is characterized by essentially normal hemodynamics in adult dogs studied at rest and in response to catecholamines in the conscious state. At the cellular level, reduced affinity and increased beta-adrenergic receptor number characterized the LV hypertrophy group, while the EC50 for isoproterenol-stimulated adenylate cyclase activity was normal. By these mechanisms, adequate responsiveness to catecholamines is retained in conscious dogs with severe LV hypertrophy.